Social support and resilience among adolescents in orphanages - Lasamahu, Felly Zefanya (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Teenagers residing in orphanages typically consist of those who have experienced the loss of their family, particularly their parents due to death or separation. This is often influenced by unfavorable economic circumstances, chaotic or disharmonious family conditions, parents' limited capacity to provide care and meet their children's basic needs, and the breakdown of the family unit, resulting in diminished parental attention. Resilience may help teens overcome the challenges they confront in life. An individual's resilience is shaped by several circumstances, both external and internal. Social support is among the many external influences. This study employs a quantitative research approach, namely using correlation analysis, to ascertain the connection between social support and resilience in juvenile orphanages. The study used the Connor-Davidson Resilience Scale (CD-RISC) and Social Support as the measuring tools. The data analysis strategy used in this study utilizes the Pearson product moment test to examine the correlation between two variables. The study findings indicate a notable and favorable correlation between social support and resilience in juvenile orphanages located in the city of Ambon. In order to enhance and broaden the area of study, it is desirable to perform additional studies on the same issue, specifically focusing on the variables that impact resilience in teenagers.